Rapid detection of phenotypes Bombay se del and nonsecretor rs200157007 SNP (302C > T) by real-time PCR-based methods - Mikiko Soejima (Nature Portfolio, 2021)
Abstract The se del allele is one of the nonsecretor alleles (se) of FUT2 generated by an Alu-mediated recombination event and was first found in Indian Bombay phenotype individuals who have anti-H, anti-A, and anti-B antibodies in their serum. As well as anti-A, and anti-B antibodies, anti-H is clinically significant because it causes sever hemolytic transfusion reactions. Like se del , se 302 having a missense single nucleotide polymorphism (SNP), 302C > T, is characteristic of South Asians with a frequency of 10–30%. We developed a real-time PCR melting curve analysis for detection of se del using a 127-bp amplicon encompassing the breakpoint junction. In addition, by performing duplex PCR by amplifying a 65-bp amplicon of the FUT2 coding region at the same time, we could determine the zygosity of se del in a single tube. We also developed an Eprobe-mediated PCR assay (Eprobe-PCR) for detection of 302C > T of FUT2. These methods were validated by analyzing 58 Tamils and 54 Sinhalese in Sri Lanka. Both the duplex PCR melting curve analysis for determination of se del zygosity and the Eprobe-PCR assay for detection of 302C > T exactly determined three genotypes. In addition, the results of the present methods were in complete agreement with those obtained by previously established methods. The two present methods were reliable and seem to be advantageous for large-scale association studies of FUT2 polymorphisms in South Asian populations.